Food Safety: Five Steps to Food Safety - Jennifer Hillan; Linda B. Bobroff (EDIS)
This 1-page fact sheet that discusses basic food safety tips for consumers is a minor revision. It was written by Jennifer Hillan and Linda B. Bobroff, and published by the Department of Family, Youth and Community Sciences, August 2017.